2009
DOI: 10.1136/gut.2009.191320
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis is characterised by local invasion with Fusobacterium nucleatum/necrophorum

Abstract: Local infection with Fusobacterium nucleatum/necrophorum is responsible for the majority of cases of acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
343
6
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(376 citation statements)
references
References 32 publications
15
343
6
12
Order By: Relevance
“…nucleatum is a known proinflammatory pathogen (20,29,43), and it was of interest to determine if the F. nucleatum strains also stimulated the proinflammatory cytokines TNF-␣ and IL-1␤. As shown in Fig.…”
Section: F Nucleatum Infection Of Ls 174t Cells Induces Mucin and Tnmentioning
confidence: 99%
See 1 more Smart Citation
“…nucleatum is a known proinflammatory pathogen (20,29,43), and it was of interest to determine if the F. nucleatum strains also stimulated the proinflammatory cytokines TNF-␣ and IL-1␤. As shown in Fig.…”
Section: F Nucleatum Infection Of Ls 174t Cells Induces Mucin and Tnmentioning
confidence: 99%
“…Thus, interference with mucin integrity is a potential strategy whereby pathogenic bacteria in the gut might gain an advantage over the host. The non-spore-forming, anaerobic, Gramnegative bacterial species Fusobacterium nucleatum is both a normal inhabitant of the human mouth and gut and a recognized opportunistic pathogen implicated in inflammatory diseases of both the mouth, such as periodontitis, and the gut, such as appendicitis and IBD (36,40,43). F. nucleatum, as a species, is highly heterogeneous, and it has been shown that some strains behave as pathogens while others are more benign; however, the basis for these differences is currently not known (18,19).…”
Section: Inflammatory Bowel Disease (Ibd) Is An Umbrella Term For a Gmentioning
confidence: 99%
“…Very recently, a critical role for Fusobacterium nucleatum/ necrophorum was postulated. 6 The immunologic reactions to preclude bacterial translocation and systemic complications like sepsis are mainly unclear. Under normal conditions, epithelial defense mechanisms prevent intestinal infection and/or translocation against the multitude of different bacteria and fungi colonizing the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two North American studies in 2012 showed overrepresentation of Fusobacterium nucleatum in colorectal cancer tumors versus surrounding normal tissue (10,15). F. nucleatum is a highly invasive, gram-negative anaerobic bacterium and part of the oral and gut commensal microbiota that has been linked to several diseases, such as appendicitis (16) and inflammatory bowel disease (17). This bacterium may contribute to colorectal cancer development by invading colonic mucosa and inducing local inflammation and increased expression of cytokines, leading to colorectal disease (18).…”
Section: The Colon Cancer Microbiome In the Context Of Human Intralummentioning
confidence: 99%